ANALISIS DAMPAK HARGA MINYAK MENTAH DUNIA, TINGKAT SUKU BUNGA DAN KURS VALUTA ASING TERHADAP INDEKS HARGA SAHAM PERTAMBANGAN PERIODE 2014 – 2016 - Jessica Prania Suradi; Selly Eriska Marisa (Jurnal Bina Manajemen, 2020)
This study aims to look at the effect of world crude oil prices, interest rates, and foreign exchange rates on the mining sector stock price index for the 2014-2016 period. The research method used is descriptive statistical methods with quantitative research types. This study also uses analytical methods such as multiple regression analysis through t test and F test. Based on the F test (simultaneous) shows that world oil prices, interest rates, and foreign exchange rates affect simultaneously on the mining sector stock price index for the period 2014-2016 , while the t test (partial) shows that world crude oil prices a positive but not significant effect on the mining stock price index for the period 2014-2016, the interest rate has a negative effect and significant to the mining sector stock price index for the period 2014-2016, and the foreign exchange rate has a negative and significant effect on the price index mining sector shares in the 2014-2016 period.